2012
DOI: 10.1080/00380768.2012.670864
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of rice bran incorporation in paddy soil on germination ofMonochoria vaginalisand its relationship with electric conductivity

Abstract: Laboratory experiments were conducted to investigate (1) the effects of the addition of rice (Oryza sativa. L.) bran to paddy soil on the germination of Monochoria vaginalis (Burm. f.) Kunth, and (2) the relationship between the electric conductivity (EC) of the soil solution and germination. Soil samples were collected at 4 sites in Japan. After flooded soils with rice bran had been incubated for 7 d at 30 C, the soil solution was collected using a porous cup and the EC of the soil solution was measured. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
3
14
0
Order By: Relevance
“…The soil solution EC (SSEC) is highly correlated with other soil properties, including the level of organic matter and salinity, which also affect crop productivity (Grisso, 2009). The application of rice bran also increases SSEC, suppressing the germination of M. vaginalis (Nozoe et al, 2012). Since PM is also organic matter similar to rice bran, its application may increase SSEC and reduce the occurrence of M. vaginalis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The soil solution EC (SSEC) is highly correlated with other soil properties, including the level of organic matter and salinity, which also affect crop productivity (Grisso, 2009). The application of rice bran also increases SSEC, suppressing the germination of M. vaginalis (Nozoe et al, 2012). Since PM is also organic matter similar to rice bran, its application may increase SSEC and reduce the occurrence of M. vaginalis.…”
Section: Introductionmentioning
confidence: 96%
“…In organic rice farming where no herbicides are applied, rice bran is often used for weed control. The addition of rice bran to the soil increases its electrical conductivity (EC) (Nozoe et al, 2012). The soil solution EC (SSEC) is highly correlated with other soil properties, including the level of organic matter and salinity, which also affect crop productivity (Grisso, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that EC increased with the decrease in soil Eh (oxidation-reduction potential) (Nozoe et al, 2012), and Nakai and Toritsuka (2009) have reported that the decrease in soil Eh with rice bran was completed over a 4-day period of cultivation. Presumably, the suppression of M. vaginalis with the increase in EC began immediately after transplanting.…”
Section: Crop Rotationmentioning
confidence: 99%
“…Although many factors, some unknown, could be associated with the decrease in the number of the M. vaginalis with the application of rice bran, these factors have not been identified. In the previous report, we suggested that the addition of rice bran to flooded soil suppressed the germination of M. vaginalis (Nozoe et al, 2012) and also that the EC of the soil solution is useful as a chemical indicator of the suppression of M. vaginalis growth. Generally, the amounts of substances such as Fe 2+ (Nozoe et al, 2008) and aromatic carboxylic acids (Tanaka et al, 1990) increase in flooded soil, and these substances sometimes suppress the growth of paddy rice.…”
Section: Analysis Ii: Effect Of Application Of Rice Bran On Ssvw and mentioning
confidence: 99%
See 1 more Smart Citation